Структурно-аналітичні моделі методу маніпулятивного впливу - Поліщук, Юлія; Гнатюк, Сергій (Видавництво Львівської політехніки, 2016)
In this paper offer the structural-analytical models of manipulative influence. Due to the synthesis of formal mass media presentations; influence channels and information Environment; coefficient cortege of information quality this models dive an opportunity to estimate mass media influence efficiency on the person and social group.
Keywords: моделі впливу; маніпулятивний вплив; мас-медіа